COVID-19: Epidemiology and virology - Antariksh Deep; Aparna Yadav; Madhu Sharma; Kundan Mittal; Anupama Mittal (Wolters Kluwer Medknow Publications, 2020)
The novel coronavirus (CoV), termed Severe Acute Respiratory Syndrome related CoV-2 (SARS CoV-2), responsible for an outbreak of unusual viral pneumonia in Wuhan city, Hubei province, China is a testimony to the risk the CoVs pose to the public health. In this review, a brief introduction of the human CoVs (hCoV), along with the epidemiology and pathogenesis of the infection caused by the hCoVs, especially the SARS-CoV-2, shall help in the understanding of the COVID-19.